Study of defects generated from a nitridation of GaAs surface - Park, YJ; Kim, EK; Han, IK; Min, SK; OKeeffe, P; Mutoh, H; Munekata, H; Kukimoto, H (ELSEVIER SCIENCE BV, 1997)
Defects studies have been performed on nitrided GaAs with deep level transient spectroscopy (DLTS) and photoluminescence (PL) measurements. Thin nitrided GaAs was formed by the irradiation of nitrogen electron cyclotron resonance (ECR) plasma at various substrate temperatures ranging from room temperature to 600 degrees C, Two electron deep levels, N1 (E-c - 0.13 eV) and N2 (E-c - 0.58 eV), related to thermal assisted nitridation induced defects were observed in the GaAs nitrided at 600 degrees C while no additional point defects were generated at nitridation temperatures up to 450 degrees C, Several deep levels such as N1 and N2 are also found to be remarkably reduced by rapid thermal annealing at 750 degrees C without any significant surface degradations. From analysis of the trap concentration and its variations with anneal temperature, the nitridation temperature of 450 degrees C followed by rapid thermal annealing at around 750 degrees C is found to be the optimum condition for nitridation without the generation of thermally assisted nitrogen plasma-induced defects. The V-As related complex and low energy ion beam induced defects are discussed as the probable sources for the N1 and N2 level defects, respectively.
Keywords: GAN; GROWTH; EPITAXY; SYSTEM; FILMS